By any other name? The impacts of differing assumptions, expectations, and misconceptions in bringing about resistance to student-staff partnership - Healey, Ruth L; Lerczak, Alex; Welsh, Katharine; France, Derek (International Journal for Students as Partners, 2019)
Most of the existing literature on student-staff partnership explores the experiences of people who are keen to be involved and who have already bought into the ethos of Students as Partners. We explore the challenges of conducting student-staff partnership in the context of resistance. Specifically, we focus on the interpretations of partnership by students and staff who were attempting to work in partnership for the first time in a medium-sized geography department in the UK The views of participants were captured during a six-month project in which four undergraduate students were employed to work with eight academics to redesign the second-year undergraduate curriculum of one programme. Notwithstanding an introductory briefing and ongoing support, some participants showed indications of resistance. Our findings suggest that different perspectives on partnership influenced participants’ experiences. We argue that assumptions, expectations, and misconceptions around the terminology used to describe Students-as-Partners practice may hinder the process itself, as some people may not buy in to the practice. However, despite the challenges of this project, the experience of being involved in the re-design of the modules has led to reduced resistance and emerging partnership practices throughout the department.